2015
DOI: 10.1097/md.0000000000001603
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Body Mass Index and Prostate Cancer at Biopsy is Modified by Genetic Risk

Abstract: Herein, we aimed to examine whether the association of body mass index (BMI) with prostate cancer (PCa) at biopsy differs according to genetic susceptibility.In a multicenter prospective cohort including 1120 men undergoing diagnostic prostate biopsy in China, we evaluated the interaction between BMI and genetic risk score (GRS) comprising 24 PCa-associated single nucleotide polymorphisms (SNPs), as well as a GRS consisting of 7 SNPs derived from an East-Asian population. The genetic risk was defined as low, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…However, no significant difference (p > 0.05) was observed in the height between the two groups. These findings are in support of the work of some researchers [13,14]. In the recent time, some associations have been found to exist among other indicators such as waist circumference (WC), waist-hip ratio (WHR), and abdominal obesity [15].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, no significant difference (p > 0.05) was observed in the height between the two groups. These findings are in support of the work of some researchers [13,14]. In the recent time, some associations have been found to exist among other indicators such as waist circumference (WC), waist-hip ratio (WHR), and abdominal obesity [15].…”
Section: Discussionsupporting
confidence: 86%
“…Obesity (BMI > 30 kg/m 2 ) is associated with an increased risk of several cancers, but conflicting results have been reported by researchers on the association between BMI and risk of PrCa. While some reported a significant interaction between BMI and PrCa [13], others reported no association between height, BMI, and risk of PrCa [14]. Result obtained from this study showed a significant increase (p < 0.05) in weight and BMI among people living with PrCa when compared to the control group (Table 1).…”
Section: Discussionmentioning
confidence: 51%
“…Evidence from published studies appears to suggest a dual effect of high BMI on PCa risk: an increased risk of aggressive PCa and a decreased risk of localized PCa . However, most of these studies reported the association with static BMI measurements, that is, BMI measured at baseline, cumulative averages over time, or at most changes in BMI between two time‐points . Evidence derived from these types of studies may be adequate to understand PCa risk with a static perspective, but obviously inadequate to capture the relevant etiologic window of PCa as the prostate carcinogenesis is a protracted course which can initiate as early as in the third decade of life .…”
Section: Introductionmentioning
confidence: 99%
“…11 However, most of these studies reported the association with static BMI measurements, that is, BMI measured at baseline, cumulative averages over time, or at most changes in BMI between two time-points. [11][12][13][14][15][16] Evidence derived from these types of studies may be adequate to understand PCa risk with a static perspective, but obviously inadequate to capture the relevant etiologic window of PCa as the prostate carcinogenesis is a protracted course which can initiate as early as in the third decade of life. 17,18 Therefore, associating dynamic longitudinal patterns in BMI with PCa may better capture the true underlying effect of body weight change on the risk of incident PCa.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Although much lower than that in Western countries and USA, the incidence of prostate cancer in the Asia has been rapidly increasing over the past few decades, including Indonesia. [7][8][9] People with prostate adenocarcinoma in Asia based on Globocan in 2008 were 122.000 patients. 10 In Indonesia based on Indonesian Society of Urologic Oncology in 2011 there were 971 patients.…”
Section: Introductionmentioning
confidence: 99%